Modelling of tidal effect on suspended sediment dispersion at Sungai Batu Pahat, Johor - Ismail, Muhamad Aqmarr Norhakim (2006)
As part of an effort to understand and predict the nutrients dynamics in Sungai Batu Pahat, the transport of sediment has been studied by combining numerical model with an extensive fields program. Oversupply of sediment loads from multiple sources will cause unstable conditions to rivers, lakes, and shallow coastal and estuarine areas. Sediment transport also brought together sorbs chemical that will distract ecosystem in the water and human daily activity such as recreation and water supply. For this research, applications of Water Quality Simulation Program 5 or WASP5 have been used to simulate suspended sediment dispersion at Sungai Batu Pahat. TOXI5 is a WAPS5’s kinetic model that has been specialized for toxic pollutants including sediment. TOXI5 is link to hydrodynamic model DYNHYD5. In this study, several analyses were conducted to determine magnitude and spatial distribution of suspended sediment in Sungai Batu Pahat due to real observation data. Results showed that there is a significant changes to sediment concentration due to tidal effect in this study